Research on the Architecture of a Basic Reconfigurable Information Communication Network - Ruimin Wang; Lei Zhuang; Yuqiang Luo; Hongchang Chen (Discrete Dynamics in Nature and Society)
The current information network cannot fundamentally meet some urgent requirements, such as providing ubiquitous information services and various types of heterogeneous network, supporting diverse and comprehensive network services, possessing high quality communication effects, ensuring the security and credibility of information interaction, and implementing effective supervisory control. This paper provides the theory system for the basic reconfigurable information communication network based on the analysis of present problems on the Internet and summarizes the root of these problems. It also provides an in-depth discussion about the related technologies and the prime components of the architecture.